Orientation rotation behavior during in situ tensile deformation of polycrystalline 1050 aluminum alloy - Han, JH; Jee, KK; Oh, KH (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Microstructural evolutions and orientation rotation behavior taking place during uniaxial tensile deformation at room temperature are studied in polycrystalline 1050 aluminum alloy. Specimens are elongated in an in situ deformation stage equipped in a high-resolution electron backscattered diffraction (HR-EBSD) system. Variations in gain boundary characteristics, such as misorientation and grain boundary distribution, during in situ tensile deformation are analyzed statistically using HR-EBSD. Orientation rotation behavior in individual grains is traced during the whole deformation process. A large number of grains in polycrystalline 1050 aluminum alloy rotate during deformation and are divided into subgrains due to multiple slip. The plane normal directions of individual grains show no remarkable tendency of the orientation rotation during in situ tensile deformation, while the orientation rotation of the tensile direction is found to be strongly dependent on the initial orientation of each grain prior to deformation. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: BACK-SCATTER DIFFRACTION; X-RAY-DIFFRACTION; SINGLE-CRYSTALS